Automatic event detection in basketball using HMM with energy based defensive assignment - Keshri, S.; Oh, M.-H.; Zhang, S.; Iyengar, G. (Journal of Quantitative Analysis in Sports, 2019)
We propose a unsupervised learning framework for automatically labeling events in a basketball game. Our framework uses the the optical player tracking data in the NBA. We first learn the time series of defensive assignments using a novel player and location dependent attraction based model which uses hidden Markov models (HMMs), Gaussian processes, and a "bond breaking" model for changes in defensive assignments. Next, we use the learned defensive assignments as an input to a set of HMMs that automatically detect events such as ball screens, drives and post-ups. We show that our models provide significant improvements over existing benchmarks both on defensive assignments and event detection.